Globalized accounting profession and the U.S. certified public accountancy - Pekdemir, Recep (Journal of Accounting, Business and Finance Research, 2024)
Globalization has affected the accounting profession most throughout the world. In today’s environment, many international accountants have recently become Chartered Accountants (CA) of the United Kingdom or Certified Public Accountants of the United States and Territories, even though they do not live in those countries. In addition, the number of international candidates has been increasing gradually, and they should know how to be licensed for one or both of those designations. In this context, the paper argues how anglophone accounting institutes and associations of English-speaking countries overwhelmingly have impacted the global accounting profession during the last two decades. In addition, it discusses the requirements for international candidates to become a Certified Public Accountant (CPA) in the United States. Consequently, the paper summarizes and documents the education requirements for international candidates who want to be licensed as a certified public accountant in the United States. National and global stakeholders, such as accounting students, accounting organizations, and regulators, may find this helpful information.